EXPERIENTIAL MARKETING AND USER-GENERATED CONTENT AS PREDICTORS OF REPURCHASE INTENTION IN LOCAL-CULTURE RESTAURANTS - Robi Rojaya Simbolon; Mukaram Mukaram; Hidya Indira Lastari (ECOBISMA (JURNAL EKONOMI, BISNIS DAN MANAJEMEN), 2026)
PURPOSE - The increasingly competitive culinary industry in Indonesia has encouraged restaurants to strengthen customer retention through experience-based and digital marketing strategies. This study aims to examine the partial and simultaneous effects of experiential marketing and user-generated content on consumer repurchase intention at a local-culture-based experiential restaurant in Bandung, West Java.METHODOLOGY - This study employed a quantitative approach with a cross-sectional explanatory survey design. Data were collected through structured questionnaires from 170 valid respondents who had visited the restaurant and had been exposed to related UGC. The data were analyzed using multiple linear regression with SPSS.FINDING – The results show that experiential marketing has a positive and significant effect on RI (β = 0.514; t = 14.286; p < 0.001). User-generated content also has a positive and significant effect on RI (β = 0.541; t = 15.019; p < 0.001), making it the slightly stronger predictor. Simultaneously, experiential marketing and user-generated content significantly predict RI (F = 437.589; p < 0.001) with strong explanatory power (Adjusted R² = 0.838). These findings indicate that authentic in-store experiences and peer-generated digital content complement each other in encouraging consumer repurchase intention.